2022
DOI: 10.1002/casp.2612
|View full text |Cite
|
Sign up to set email alerts
|

Interagency collaboration among community organizations serving children and families in child welfare

Abstract: Transformational change to address adversity and nurture resilience requires deep and sustained community collaborations. Interagency collaboration is critically important for child welfare especially during crisis situations. It is clear that when agencies focus on strengths and promote protective factors (individual, familial and community-level) in time, negative consequences of maltreatment are reduced and wellbeing outcomes are enhanced. However, limited research is available to effectively inform communi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 44 publications
2
7
0
Order By: Relevance
“…These findings are corroborated by Kothari et al. (2022) who found that participants from community organisations mentioned noteworthy and positive impacts brought on by the pandemic such as unanticipated opportunities to learn new skills and increase creativity with regard to providing services to children and families. Their findings indicated clear strengths to collaboration among community organisations focused on child welfare (e.g., strong connections, resource sharing, resilience in staff, more vulnerable children accessing resources and more adults engaged in serving this population).…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…These findings are corroborated by Kothari et al. (2022) who found that participants from community organisations mentioned noteworthy and positive impacts brought on by the pandemic such as unanticipated opportunities to learn new skills and increase creativity with regard to providing services to children and families. Their findings indicated clear strengths to collaboration among community organisations focused on child welfare (e.g., strong connections, resource sharing, resilience in staff, more vulnerable children accessing resources and more adults engaged in serving this population).…”
Section: Discussionsupporting
confidence: 67%
“…Similarly, practices in the Interagency Collaboration domain such as 'coordinating interagency agreements between schools and outside agencies' and 'collaborating with agencies to share funding and staffing for transition services' and practices in the Leadership and Policy domain such as 'ensuring teachers implement federal and state policies related to transition' and 'using evidence based practices and research to develop transition programs' could fall within the same rationale. These findings are corroborated by Kothari et al (2022) who found that participants from community organisations mentioned noteworthy and positive impacts brought on by the pandemic such as unanticipated opportunities to learn new skills and increase creativity with regard to providing services to children and families. Their findings indicated clear strengths to collaboration among community organisations focused on child welfare (e.g., strong connections, resource sharing, resilience in staff, more vulnerable children accessing resources and more adults engaged in serving this population).…”
Section: Discussionmentioning
confidence: 59%
“…The current findings about the centrality of organisational agility and community involvement and the need for improved stakeholder collaboration cohere with Masten and Motti-Stefanidi’s (2020) multi-system resilience perspective, whereby children’s capacity to respond adaptively to adversity is contingent upon the interconnected influence of supportive organisations, communities, peers and families. Those dispersed and relational aspects of resilience, and particularly its fragility during emergencies, are acutely evident upon dissecting the successes and failures in, and lessons learned from, intersectoral collaboration (Kothari et al , 2022; Gilson et al , 2017). While the present study highlights its centrality and dynamics, future research should more systematically examine the mechanisms underpinning intersectoral and interagency collaboration and their impact on organisational and individual resilience (Jewett et al , 2021; Kothari et al , 2022; Ortenzi et al , 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Those dispersed and relational aspects of resilience, and particularly its fragility during emergencies, are acutely evident upon dissecting the successes and failures in, and lessons learned from, intersectoral collaboration (Kothari et al , 2022; Gilson et al , 2017). While the present study highlights its centrality and dynamics, future research should more systematically examine the mechanisms underpinning intersectoral and interagency collaboration and their impact on organisational and individual resilience (Jewett et al , 2021; Kothari et al , 2022; Ortenzi et al , 2022). As Gilson and colleagues (2017, p. 2) argue, “[r]esilience is not a function of what a system has but of what it does and how it does it”.…”
Section: Discussionmentioning
confidence: 99%
“…The editorial team welcomes research from all areas of community and social psychology. We accept empirical, theoretical, and methodological articles, and welcome a wide range of methodologies, including quantitative (Pecini et al, 2022), qualitative (Varma & Siromahov, 2023), and mixed methods research (Kothari, Fischer, Mullican, Lipscomb, & Jaramillo, 2022), as well as correlational (Gray, Randell, Manning, & Cleveland, 2023), longitudinal (Joshanloo, 2022), and experimental designs (Mäkinen et al, 2022). Relatedly, we have expanded the types of articles that we accept.…”
mentioning
confidence: 99%